2018
DOI: 10.1007/s13524-018-0672-9
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Neighborhood Choice in a Model of Neighborhood Effects on Income

Abstract: Studies of neighborhood effects often attempt to identify causal effects of neighborhood characteristics on individual outcomes, such as income, education, employment, and health. However, selection looms large in this line of research, and it has been argued that estimates of neighborhood effects are biased because people nonrandomly select into neighborhoods based on their preferences, income, and the availability of alternative housing. We propose a two-step framework to disentangle selection processes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 30 publications
0
38
0
Order By: Relevance
“…They are often expressed in terms of transition matrices linking categories of origin and destination neighborhoods by some indicator of interest (e.g., Clark et al 2014). 4 Kim, Pagliara, and Preston (2005) (Kim et al 2005;Lee and Waddell 2010;van Ham et al 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are often expressed in terms of transition matrices linking categories of origin and destination neighborhoods by some indicator of interest (e.g., Clark et al 2014). 4 Kim, Pagliara, and Preston (2005) (Kim et al 2005;Lee and Waddell 2010;van Ham et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…4 Using this approach, many studies have found that households are more likely to be attracted to neighborhoods where higher percentages of their own income and/or racial-ethnic group are present (cf. Boschman and van Ham 2015;Hedman 2013;Hedman et al 2011;Ioannides andZabel 2003, 2008;Kim et al 2005;Lee and Waddell 2010;Sermons and Koppelman 2001;Spring et al 2017;Steele et al 2016;van Ham et al 2018). 5 Unfortunately, none of the aforementioned works measures multiple dimensions of neighborhoods' income composition, confining themselves to measures like poverty rates and median family incomes.…”
Section: Background Literature and Our Contributionmentioning
confidence: 99%
“…From the multinomial logit model, we derive the linear probabilities reflecting the likelihood that an individual belong to a certain type of congregation (Van Ham and al., 2018). Following Ioannides and Zabel (2008), we transform these linear probabilities to generate correction terms akin to the inverse Mills ratios popularized by Heckman's (1979) two-stage regression framework.…”
Section: The Selection Modelmentioning
confidence: 99%
“…We use data from the U.S. Congregational Life Survey and a multilevel approach to evaluate congregation effects. The problem with estimating congregation effects on poverty is that people are nonrandomly allocated to congregations: people select into groups based on their preferences and resources (Van Ham and al., 2018). That is, people tend to move to congregations that match their preferences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation